Um estudo de rede social como um caminho de participação cidadã: a experiência da Rede Social Campo Grande São Paulo 2004-2008 - Toro, Maria Izabel Costa Monte Alegre (2009)
The theme of this dissertation is analysis of the formation of strategic networks in the context of contemporary globalization and the resulting social, economic and technological impacts. The study focused on social networks and the object was the participatory process in Social Network Campo Grande - SP, an initiative promoted by Senac São Paulo and analyzed in the period of 2004 through 2008. The general goal was to understand and analyze the trajectory of the network in the four years of its operations in the south of São Paulo, in relation to stimulation of citizen participation. The conceptual frameworks were: globalization, social networks and citizen participation, based on national and foreign authors, especially from the social sciences. The methodological procedures used in this study were: reflection and research literature on the topic of social networks and citizen participation; documentary research about Senac-SP and Social Network Campo Grande SP, field research which included researcher participation in network meetings as well as the development of criteria and definitions for nine participants to use in conducting semi-structured interviews and transcription and organization of data collected on the central question of citizen participation. The research demonstrated that the Social Network Campo Grande struggles to integrate citizen participation through, representatives of NGOs, municipal authorities and local residents, especially through the formation of social ties and collective action in joint projects and actions that expand the participatory process, and also presenting an understanding of limits on citizen participation as a social right